2000
DOI: 10.1103/physrevlett.84.733
|View full text |Cite
|
Sign up to set email alerts
|

Inverted Electron-Hole Alignment in InAs-GaAs Self-Assembled Quantum Dots

Abstract: New information on the electron-hole wave functions in InAs-GaAs self-assembled quantum dots is deduced from Stark effect spectroscopy. Most unexpectedly it is shown that the hole is localized towards the top of the dot, above the electron, an alignment that is inverted relative to the predictions of all recent calculations. We are able to obtain new information on the structure and composition of buried quantum dots from modeling of the data. We also demonstrate that the excited state transitions arise from l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
288
9
4

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 491 publications
(342 citation statements)
references
References 15 publications
38
288
9
4
Order By: Relevance
“…The results of measurements of the photocurrent absorption spectrum as a function of applied bias, where both the magnitude of absorption and energy of the peak of the absorption spectrum change, have been interpreted as evidence of a change in the electron and hole wave function overlap due to the quantum confined Stark effect. 14,15 However, in such measurements with our samples we observe no change in the energy of the peak of the absorption spectrum as a function of applied bias 16 indicating that the overlap of the electron and hole wave functions is insensitive to the local electric field in our samples. The modeling of quantum well structures, for example, 17 based on the self-consistent solution of the Schrodinger-Poisson equations and with carrier density dependent broadening of the Fermi golden rule optical gain spectrum, suggests that the electrostatic deformation of energy bands ͑here described as a relative movement of the quasi-Fermi levels and included within f c − f v ͒ has a much larger effect than the carrier density dependent homogenous broadening.…”
Section: Calculationsmentioning
confidence: 83%
“…The results of measurements of the photocurrent absorption spectrum as a function of applied bias, where both the magnitude of absorption and energy of the peak of the absorption spectrum change, have been interpreted as evidence of a change in the electron and hole wave function overlap due to the quantum confined Stark effect. 14,15 However, in such measurements with our samples we observe no change in the energy of the peak of the absorption spectrum as a function of applied bias 16 indicating that the overlap of the electron and hole wave functions is insensitive to the local electric field in our samples. The modeling of quantum well structures, for example, 17 based on the self-consistent solution of the Schrodinger-Poisson equations and with carrier density dependent broadening of the Fermi golden rule optical gain spectrum, suggests that the electrostatic deformation of energy bands ͑here described as a relative movement of the quasi-Fermi levels and included within f c − f v ͒ has a much larger effect than the carrier density dependent homogenous broadening.…”
Section: Calculationsmentioning
confidence: 83%
“…On the other hand, if pure InAs is deposited as epilayer material, the resulting islands may consist of InGaAs: Joyce et al have found evidence for alloying in uncapped InAs islands on GaAs for growth temperatures above 420 ± C, and thus have suggested that significant Ga mass transport occurs [9]. Indeed recent investigations of the electronic properties indicate substantial composition gradients [10].…”
mentioning
confidence: 99%
“…It has been shown [53] that if the QD possesses a permanent dipole, the energy shift induced by the applied field has a linear component as well as the usual quadratic component arising from the polarizability. Such a permanent dipole is induced by the spatial separation between the electron and hole wave functions.…”
Section: Quantum-confined Stark Effect (Qcse)mentioning
confidence: 99%